Substance use and adolescent injuries: a multi-country analysis of the association and mediating effect of interpersonal violence among 122,945 in-school paediatric populations in 29 countries - Adjei, Benjamin Noble; Afetor, Maxwell; Ansong-Aggrey, Samuel; Okwei, Reforce; Nachibi, Stephen Uwumbordo; Munkaila, Lambongang; Arimiyaw, Abdul Wahid; Osei Bonsu, Emmanuel; Adu, Collins; Peprah, Prince (Frontiers in Public Health, 2023)
Background Adolescent use of substances and injury experiences such as head injury have become increasingly prevalent. However, information regarding their association and the potential pathways linking them remains limited. This study examined the association between substance use and injuries, emphasizing the mediating role of interpersonal violence among adolescents. Methods We employed a multi-country analysis of Global School-based Health Surveys of 122,945 in-school adolescents aged 11–18 from 29 countries. This study was a cross-sectional school-based, nationally representative study developed by the World Health Organization and the United States Centers for Disease Control and Prevention, other United Nations allies, and country-specific institutions. Random-effects meta-analysis was performed to estimate the overall prevalence of injury and substance use and the I-square (I2) statistic was used to investigate the between-country heterogeneity. Logistic regression models were fitted to examine the association between substance use and injuries. A path analysis was used to examine the potential mediation effect of interpersonal violence and employed decomposition of effects into total, direct, and indirect. Results Prevalence of substance use and injuries were 33.6% (95%CI = 28.5, 38.6%) and 41.7% (95%CI = 37.3, 46.1%), respectively. Substance use (37.8% vs. 29.4%, p = 0.001) and injuries (47.3% vs. 36.4%, p = 0.001) were significantly higher among male adolescents than females, respectively. After adjustment, substance users had 40% higher odds of injuries. The path analysis showed a mediation effect of perpetration of and victimization by interpersonal violence on the association of substance use with injuries, with total positive effects of perpetration [β = 0.18; 95%CI = 0.16, 0.19; p = 0.001] and victimization on injuries [β = 0.22; 95%CI = 0.21, 0.24; p = 0.001]. In a further subgroup analysis, tobacco users were 3.98 times more likely to sustain a gunshot wound whiles marijuana users had 2.81 times higher odds of sustaining gunshot wounds. Cigarette smokers had 45% lower odds of sustaining cut/stab wounds. Alcohol users were 53% more likely to sustain concussion/head injury and two and half times more likely to sustain gunshot wound. Conclusion A significant association exists between substance use and severe injuries among adolescents, mediated by interpersonal violence exposure. Our findings may have utility in informing substance use and interpersonal violence control policies and interventions to address adolescent injuries.